Effects of First and Second Flower Stamps on Growth and Production of Hybrid Pepper (Capsicum annuum L) Mace Varieties - Astoko, Endro Puji (Prosiding Seminar; 2019: 2019 International Conference of Interdisciplinary Sciences, 2020)
Chili is a shrub from the family of eggplant that has the scientific name Capsicum sp . The purpose of this study was to determine whether the first and second flower vines could stimulate vegetative growth of hybrid chili ( Capsicum annuum L ) varieties. Gada Experiment was carried out in Sumberurip Hamlet, Manggis Village, Ngancar District, Kediri Regency on dry land with Latosol soil type (sandy cane) and pH 6.0. The height of the place from sea level is around 450 above sea level, the average annual rainfall is 1,785 millimetres with 85 rainy days. The average temperature is 29Â°C and the type of climate is C3. The experiment was conducted from December 1, 2009 to February 30, 2010. The results of the study: the first and second flower flowering treatments in the hybrid red pepper variety of Gada significantly affected the fruit diameter and significantly affected the plant height at 70 days, the number of tertiary branches at the age of 70 days, fruit length, and number of fruits per plant and fruit weight. The highest production was achieved in the first and second flower treatment Z (P3), which is 16.6 grams per fruit which is equivalent to 25,853.17 kg/ha.